Phosphorus fertilization and maize intercropping with peanut synergistically reshape rhizosphere microbiome and enhance crop yield - Zheng, Yan; Zhao, Wei; Hu, Xiaona; Li, Zizheng; Gao, Kaizheng; Jiao, Nianyuan (Frontiers in Microbiology, 2026)
IntroductionOptimizing nutrient cycling in diversified cropping systems is essential for sustainable agriculture. While intercropping legumes with cereals can enhance complementary resource use, the interaction between phosphorus (P) fertilization and such systems in restructuring rhizosphere microbiomes and driving synergistic productivity gains in alkaline soils remains unclear.MethodsWe conducted a long-term field experiment, integrating amplicon sequencing with comprehensive agronomic and soil analyses to investigate this interaction in a maize-peanut intercropping system under P fertilization.ResultsPhosphorus fertilization significantly increased the yields of intercropped maize (by 52.12%) and peanut (by 43.60%), while simultaneously enhancing the intercropping yield advantage (IYA; +60.77%) and land equivalent ratio (LER; +2.54%). Soil P availability was the dominant environmental driver, explaining 73.46% and 84.39% of the variance in bacterial and fungal community structure, respectively. Phosphorus addition and intercropping selectively enriched keystone functional taxa, including the nitrifying bacterium Nitrospirae and the saprophytic fungus Mortierellomycota, whose abundances correlated strongly with improved soil nutrient availability and crop performance. Concurrently, intercropping suppressed the pathogen-rich phylum Ascomycota.DiscussionOur findings demonstrate that the synergy between P fertilization and intercropping enhances crop productivity through a microbiome-mediated mechanism. This synergy restructures the rhizosphere community into a functionally beneficial state, fostering a self-reinforcing plant–microbe–soil feedback loop. This study provides a mechanistic framework for developing integrated, microbiome-informed management strategies to support sustainable agricultural intensification.